Didymodon rigidulus var. subulatus (Thér. & Bartram ex E.B. Bartram) R.H. Zander, new to the moss flora of Mongolia and Asia (Bangladesh Journal of Plant Taxonomy, 2015)
Not available. Bangladesh J. Plant Taxon. 22(1): 6366, 2015 (June)